2017
DOI: 10.1021/acs.jpclett.7b02312
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Dependent Potential Precycling Effects on Lithium Deposition/Dissolution Reaction Studied by an Electrochemical Quartz Crystal Microbalance

Abstract: The electrochemical quartz crystal microbalance technique was employed to study the initial stage of the electrodeposition and dissolution of lithium utilizing three kinds of electrolyte solutions such as LiPF, LiTFSI, or LiFSI in tetraglyme. The native-SEI (solid-electrolyte interphase) formed by a potential prescan before lithium deposition/dissolution in all three solutions. Simultaneous additional SEI (add-SEI) deposition and its dissolution with lithium deposition and dissolution, respectively, were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This is not the full 7 m / z expected for the state of lithiation, thus indicating consumption of Li + most likely in the formation of the SEI layer. Smaran et al found that m / z < 7 was attributed to SEI formation on the surface of Li metal in glyme-based electrolytes . The relatively slow kinetics of the Li deposition at 0.05 V would suggest that a small amount of Li deposits would react with the solvent and subsequent impurities, such as HF, resulting in a low m / z ratio …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the full 7 m / z expected for the state of lithiation, thus indicating consumption of Li + most likely in the formation of the SEI layer. Smaran et al found that m / z < 7 was attributed to SEI formation on the surface of Li metal in glyme-based electrolytes . The relatively slow kinetics of the Li deposition at 0.05 V would suggest that a small amount of Li deposits would react with the solvent and subsequent impurities, such as HF, resulting in a low m / z ratio …”
Section: Resultsmentioning
confidence: 99%
“…Smaran et al found that m/z < 7 was attributed to SEI formation on the surface of Li metal in glyme-based electrolytes. 49 The relatively slow kinetics of the Li deposition at 0.05 V would suggest that a small amount of Li deposits would react with the solvent and subsequent impurities, such as HF, resulting in a low m/z ratio. 50 Upon delithiation to 1.5 V, the SEI layer grows to 15 ± 0.2 nm with an increase in the SLD to 3.83 ± 0.05 (from 1.52), reflecting a change in the chemistry of the layer as a result of the delithiation of the anode (Table 1).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Multiple MPE values were obtained during Li plating, indicating multiple electrochemical processes. [36] An extra film was formed during Li plating due to the reaction of plated Li metal with electrolyte as indicated by MPE values much larger than 7 (a value indicating only Li plating/stripping occurs). [43] The possible surface species are the complicated organics from the decomposed TEGDME molecule and the organic Li salts from the reaction of Li metal with these organics, resulting in the overall MPE values around 50-80.…”
Section: Resultsmentioning
confidence: 99%
“…The MPE (mass change per mol e − ) values during this process, which can be calculated from the slope of the plot with Δ m as a function of the passed charge, was close to 10. It was deemed to be a result of several electrochemical reactions that generated both dissolved products and deposited products, while the latter were mostly inorganic species, especially Li 2 O which could be a product of the reductive decomposition of LiTFSI (Li 2 O as one of the final products, MPE unknown), [36,37] or the reduction of Cu oxides on the Cu surface (Cu x O+2Li→Li 2 O+ x Cu), [16] or even the reaction with trace oxygen in glove box (O 2 +4Li + +4e − →2Li 2 O, MPE=15) [38] . This could also suggest that TEGDME did not heavily decompose prior to the initial Li plating (also indicated by the weak reduction current shown in Figure S1a), since most of the decomposed fragments and derivatives of TEGDME have larger MPE values [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…The CVs exhibit negative and positive current peaks around −3.0 V in both cases. The negative and positive peaks have been assigned to lithium deposition and the dissolution of the deposited metal lithium, respectively, 36 indicating lithium deposition/dissolution takes place in both dilute and superconcentrated electrolyte solutions. While the dilute system shows almost no current peak in the potential region more positive than −2.0 V, the saturated system shows negative and small positive peaks around −1.7 and −0.7 V, respectively.…”
Section: Methodsmentioning
confidence: 99%